2022
DOI: 10.1002/mar.21639
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality filters on social media. Analyzing the drivers of playability based on uses and gratifications theory

Abstract: The arrival of augmented reality (AR) on social networks in the form of filters is generating new user experiences. Despite their potential as interactive marketing tools, previous research analyzing the impact of AR filters has focused mainly on shopping‐based or personal‐based variables. Conceiving AR filters to be entertainment products, this research follows the theory of uses and gratifications to examine the playability of AR filters, that is, the satisfaction that users derive from the experience and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 108 publications
(279 reference statements)
1
27
0
Order By: Relevance
“…Firms increasingly leverage reality-enhancing technologies to create memorable experiences and stimulate deeper engagement. Especially AR, in the form of interactive face filters or product lenses, has been integrated into existing social media platforms, including Instagram, SnapChat, and Pinterest, such that consumer-to-consumer engagement on these platforms is nowadays partially driven through AR (Ibáñez-Sánchez et al, 2022). AR enables consumers to directly try out virtual products, such as cosmetics or eyewear, which are promoted by brands or their influencers.…”
Section: Meaningful Engagement and Experiencesmentioning
confidence: 99%
“…Firms increasingly leverage reality-enhancing technologies to create memorable experiences and stimulate deeper engagement. Especially AR, in the form of interactive face filters or product lenses, has been integrated into existing social media platforms, including Instagram, SnapChat, and Pinterest, such that consumer-to-consumer engagement on these platforms is nowadays partially driven through AR (Ibáñez-Sánchez et al, 2022). AR enables consumers to directly try out virtual products, such as cosmetics or eyewear, which are promoted by brands or their influencers.…”
Section: Meaningful Engagement and Experiencesmentioning
confidence: 99%
“…Previous studies have identified specific functions which are transversal to all social media types, such as presence, sharing, relationships, or identity (Felix et al, 2017). The surge of augmented reality filters on social networks has created new user experiences that potentiate user satisfaction and sharing (Ibáñez‐Sánchez et al, 2022), while virtual reality has generated new forms of presence for individuals and firms (i.e., immersive and vivid telepresence) (C. Chen & Yao, 2022). The construction of most of these functions is facilitated by the responsiveness provided by social media platforms for consumers (Mazerant et al, 2021).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Affective storytelling is more effective in changing consumers' attitudes (Hamelin et al, 2020), as each plot in a story can be treated as a symbolic sign, subject to interpretation by the consumer (Nguyen, 2017). A brand can appeal to consumers' imagination (Abela, 2014) and curiosity (Ibáñez‐Sánchez et al, 2022) to engage with affective storytelling through aesthetic, poetic, and truthful means (McAuley & Pervan, 2014) if the narrative is intriguing and exciting to consumers (Carlsson Hauff et al, 2014).…”
Section: Resultsmentioning
confidence: 99%